[177Lu]DOTA-anti-CD20: Labeling and pre-clinical studies - Audicio, Paola F. (2011)
Anti-CD20 (Rituximab®), a specific chimeric monoclonal antibody used in CD20-positive Non-Hodgkin’s Lymphoma, was conjugated to a bifunctional quelate (DOTA) and radiolabeled with 177Lu through a simple method. [177Lu]-DOTA-anti-CD20 was obtained with a radiochemical purity higher than 97%, and showed good chemical and biological stability, maintaining its biospecificity to CD20 antigens. MonteCarlo simulation showed high doses deposited on a spheroid tumor mass model. This method shows to be an appropiate alternative for the production of [177Lu]-DOTA-anti-CD20 as therapeutic radiopharmaceutical.